Amorphous, Efficient, Room‐Temperature Phosphorescent Metal‐Free Polymers and Their Applications as Encryption Ink. Issue 9 (22nd July 2016) - Chen, Hui; Yao, Xuyang; Ma, Xiang; Tian, He
Abstract : A facile way to construct metal‐free phosphorescent amorphous polymers is developed. The resulting materials show strong room‐temperature phosphorescence (RTP) luminescence in ambient atmosphere, and phosphorescent quantum yields are achieved at a high level without extra processing. Some potential applications as encryption ink are also studied as the materials are water‐responsive and photoresponsive.